Repetitive DNA mapping on Oligosarcus acutirostris (Teleostei, Characidae) from the Paraíba do Sul River Basin in southeastern Brazil - Cunha, Marina Souza; Melo, Silvana [UNESP]; Salgado, Filipe Schitini; Assis, Cidimar Estevam; Dergam, Jorge Abdala (Firenze University Press, 2021)
Within the Neotropical region, the genus Oligosarcus represents an interest-ing assembly of small-sized freshwater predators. The goal of this study was to cytoge-netically analyze Oligosarcus acutirostris from the Espírito Santo Stream, Paraíba do Sul River Basin. The following cytogenetic techniques were performed: Giemsa stain-ing, Ag-NOR and C-bandings, Fluorescence in situ Hybridization (FISH) using 18S and 5S rDNA probes, and (CA)15 and (GA)15 microsatellite probes. Diploid number was 2n=50 and the karyotypic formula 4m+14sm+18st+14a. Ag-NOR sites were present on the subtelocentric chromosome pair number 10. C-banding showed a few peri-centromeric and conspicuous terminal heterochromatic blocks. The 18S and 5S rDNA probes marked chromosome pairs number 10 and number 19, respectively. FISH patterns obtained with (CA)15 and (GA)15 probes hybridized pericentromeric and terminal regions in almost all chromosomes, and interstitial regions of some chromosomes. Interestingly, microsatellite (CA)15 showed a conspicuous centromeric mark on chromosome pair number 14, which could be an autapomorphy of this species, or it might characterize some species of this genus. The Oligosarcus cytogenetic patterns suggest that this genus is prone to fixation of chromosomal rearrangements and may be useful to detect biogeographical subunits within the coastal Brazilian basins.
Keywords: Characiformes; Coastal river basins; Cytotaxonomy; Fluorescence in situ hybridization (FISH); Freshwater fishes